Development of a Moodle VLE Plug-in to Support Simultaneous Visualisation of a Collection of Multi-Media Sign Language Objects - LEESON, LORRAINE (My University, 2010)
Using Virtual Learning Environments (VLE) to support blended learning is very common in educational institutes. Delivering learning material in a flexible and semi-structured manner to the learner transforms such systems into powerful eLearning tools. However, the presentation and visualisation of individual or multiple learning objects is mostly dictated by the system and cannot be altered easily. This paper reports on a project between Trinity College Dublin (TCD) and the Institute of Technology Blanchardstown (ITB) that aims to improve the simultaneous visualisation of multiple multimedia objects for deaf learners of ISL. The project was implemented using the Open Source VLE Moodle. Moodle?s nature of being Open Source and having the ability to code plug-ins qualified it to be the most suited vehicle to address the visualisation problem. Traditionally VLEs allow the viewing of one learning object at a time, which meant that deaf learners could either view a pre-recorded, signed in ISL, video lecture or concentrate on textual accompanying content but not both. The developed Moodle plug-in allows academics to group multiple videos into a `lecture?. It further facilitates the addition of rich text content to each video. The learner can select and view one video from a possible sequence of many as well as view the text that belongs to the video. The paper further outlines detailed implementation and techniques applied.
PUBLISHED
Keywords: Deaf; SIF II; Leonardo da VInci; SIGNALL II; Sign Language; elearning